1976
DOI: 10.1029/ja081i016p02765
|View full text |Cite
|
Sign up to set email alerts
|

Plasma wave interactions with energetic ions near the magnetic equator

Abstract: An intense band of electromagnetic noise is frequently observed near the magnetic equatorial plane at radial distance from about 2 to 5 RE. Recent wide band wave form measurements with the Imp 6 and Hawkeye 1 satellites have shown that the equatorial noise consists of a complex superposition of many harmonically spaced lines. Several distinctly different frequency spacings are often evident in the same spectrum. The frequency spacing typically ranges from a few hertz to a few tens of hertz. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
188
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(197 citation statements)
references
References 17 publications
9
188
0
Order By: Relevance
“…Our results suggest an analogy with natural emissions of whistler-mode chorus (generally observed above f lh ), which are also very intense, and which are believed to significantly influence the dynamics of the energetic electrons in the Earth's outer radiation belt (Meredith et al, 2003;Horne et al, 2003;Horne and Thorne, 2003). According to the most accepted generation mechanism of equatorial noise (Gurnett, 1976;Perraut et al, 1982), its amplification is fed by the free energy in the distribution functions of energetic ions, which may be significantly influenced by interactions with these waves.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Our results suggest an analogy with natural emissions of whistler-mode chorus (generally observed above f lh ), which are also very intense, and which are believed to significantly influence the dynamics of the energetic electrons in the Earth's outer radiation belt (Meredith et al, 2003;Horne et al, 2003;Horne and Thorne, 2003). According to the most accepted generation mechanism of equatorial noise (Gurnett, 1976;Perraut et al, 1982), its amplification is fed by the free energy in the distribution functions of energetic ions, which may be significantly influenced by interactions with these waves.…”
Section: Discussionmentioning
confidence: 83%
“…Later observations (Gurnett, 1976;Perraut et al, 1982;Laakso et al, 1990;Kasahara et al, 1994;André et al, 2002) revealed that the equatorial noise occurs at radial distances between 2 and 7 R E , and at latitudes within 10 • from the magnetic equator, and that its lowest frequency could go down to the fundamental f H + . Detailed time-frequency spectrograms (Gurnett, 1976) also showed that, what appears as a noise band in the low resolution data, is in fact a superposition of many spectral lines with different frequency spacings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gurnett [1976] analyzed equatorial crossings in the region 2 < L < 3.5 and found that the waves were largely confined to within 5°of the magnetic equatorial plane. These waves are excluded from our survey by excluding emissions observed within ±5°of the magnetic equator.…”
Section: Identification Of Plasmaspheric Hiss and Lightning Generatedmentioning
confidence: 99%